Implementation of Story Mapping and Mind Mapping Toward Students' Reading Comprehension Enhancement: A Comparative Study - Wulandari, Novia (LPPM Universitas Advent Indonesia, 2019)
The purpose of this study is to find out significant difference in implementing Story Mapping and Mind Mapping techniques toward students’ reading comprehension enhancement. This study used a quantitative research method and comparative design by measuring the achievement of pre-test and post-test. This study addressed three research questions: (a) What is the achievement of the students after being treated with Story Mapping and Mind-mapping Techniques? (b) Is there any significant difference between Story Mapping and Mind-mapping techniques in enhancing students’ reading comprehension?, (c) What is students’ response towards Story Mapping and Mind-mapping techniques? There are different types of text in reading; however, the researcher limited the texts given to the participants,utilizing narrative and descriptive texts only. This study utilized small average amount of sample size,72 eight graders to be given the treatment. The purpose of limiting the number of participants is to provide effective treatment for them. The result of this study shows that p. value (sig) = 0.279 > Î± (0.05). After analyzing the data, the researcher found out that the students reading comprehension are enhanced but there is no significant difference in reading comprehension enhancement between those who acquired Story Mapping technique and those who acquired Mind Mapping technique. Both techniques are deemed to be effective in enhancing students’ reading comprehension. Keywords Reading comprehension, Story Mapping, Mind Mapping